Dual Education Models in Modern Educational Institutions - Kravchenko, Olha; Shpynta, Halyna; Nikolaienko, Oksana; Dovbenko, Svitlana; Diachok, Oksana (Journal of Technical Education and Training, 2023)
The aim of the research is to verify the effectiveness of the dual education in modern educational institutions. The research involved the following methods: testing method (Self-Attitude Test) and methods of studying self-assessment through the ranking procedure; the peer-review method; Human Volitional Qualities Questionnaire; Student’s t-test and the Kolmogorov-Smirnov test; Spearman's Rank correlation coefficient; Survey Response Rate calculation. Students expressed the greatest satisfaction with such aspects as the relationship with the tutor (0.84), tutor’s objectivity in work evaluation (0.91), safe working environment (0.92), individual workplace (0.89). There were 58% of respondents who favoured dual education compared to traditional education. A group of experts who studied academic performance noted the advantage of the flipped classroom-based model. The level of special competencies in the control group was 4.5 units, while it was 4.9 units in the experimental group. The results of the study showed the high efficiency of dual education based on the flipped classroom model. The research identified a more effective implementation model. This model shows significant positive results, both in the context of higher education and vocational education. Future research should be aimed at finding an effective model for implementing the dual system in vocational education. Also, it is necessary to study the effectiveness of such innovations in modern realities.